Two-stage Revision for Periprosthetic Hip and Knee Joint Infections - Kini, Sunil Gurpur (Open Orthop J, 2016)
BACKGROUND: Periprosthetic joint infection (PJI) continues to be one of the leading causes of failure following hip and knee surgery. The diagnostic workflow of PJI includes detailed clinical examination, serum markers, imaging and aspiration/biopsy of the affected joint. The goals of treatment are eradication of the infection, alleviation of pain, and restoration of joint function. Surgical management of PJI consists of debridement, antibiotics and implant retention (DAIR) and single or two-stage revision procedures. Two-stage revision remains the gold standard for treatment of PJIs. We aim to discuss the two stage procedure in this article and report the outcomes. METHODS: The first stage of the two stages consists of removal of all components and associated cement with aggressive debridement and placement of an antibiotic-loaded cement spacer. Patients are then treated with variable periods of parenteral antibiotics, followed by an antibiotic free period to help ensure the infection has been eradicated. If the clinical evaluation and serum inflammatory markers suggest infection control, then the second stage can be undertaken and this involves removal of the cement spacer, repeat debridement, and placement of a new prosthesis. RESULTS: Common themes around the two-stage revision procedure include timing of the second stage, antibiotics used in the interim period, length of the interim period before consideration of reimplantation and close liaising with microbiologists. CONCLUSION: Successful eradication of infection and good functional outcome using the two stage procedure is dependent on a multidisciplinary approach and having a standard reproducible startegy.